Hierarchical Archimedean copulae: The HAC package - Ostap Okhrin; Alexander Ristig (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
This paper aims at explanation of the R-package HAC, which provides user friendly methods for dealing with high-dimensional hierarchical Archimedean copulae (HAC). A computationally effcient estimation procedure allows to recover the structure and the parameters of HACs from data. In addition, arbitrary HACs can be constructed to sample random vectors and to compute the values of the corresponding cumulative distribution as well as density functions. Accurate graphics of the important characteristics of the package's object hac can be produced by the generic plot function.
Keywords: C51; C87; 330; copula; R; hierarchical Archimedean copula (HAC); Kopula (Mathematik); Statistische Methodenlehre; PC-Software